Projeto e análise de antenas em fenda operando em UHF para nanossatélites - (:unkn) unknown (Universidade Federal do Pampa, 2019)
This work describes a study of antennas for nano-satellites. The scenario considered for this study is the Brazilian Environmental Data Acquisition System (SBCDA), maintained by the National Institute for Space Research (INPE). The uplink of the data transmission system operates in UHF (ultra-high frequency) and the downlink in S-Band (2.26 GHz). The work begins with a literature review about antenna topologies suitable for installation onto nano-satellites. Furthermore, slot antennas and techniques for antenna miniaturization have been considered. Initially, a quarter-wavelength slot was analyzed. Such a structure presents bidirectional radiation pattern, which is not suitable in the targeted application. To overcome this limitation, the antenna has been installed onto articulable aps along with reector elements in the back, thereby resulting in an unidirectional pattern. Circular polarization was obtained by installing 4 antennas sequentially rotated by 90°, so as to compose a planar array. The second analyzed structure was a slot antenna with the application of reactive loading. The main goal was to achieve miniaturization, hence reducing the antenna area. For this purpose, an investigation on different reactive loading topologies has been carried out. The overall performance has been evaluated based on mass, operational band, gain and front-to-back ratio. Finally, a prototype was fabricated for the experimental validation of the simulated results. One of the compact antenna models was chosen, which presented the best operational results. Initially, an 8U nanosatellite engineering model was built. Then a single element was prototyped and measured. Finally, an element of the simulated antenna array was prototyped and installed onto the nano-satellite model, in order to validate the simulations.
Keywords: Engenharia de telecomunicações; Antenas; Nanossatélite; Telecomunicações; Telecomunication engeneering; Antennas; Nano-satellite; Telecommunications; CNPQ::ENGENHARIAS